2011
DOI: 10.1016/j.cej.2011.08.053
|View full text |Cite
|
Sign up to set email alerts
|

The role of unburned carbon concentrates from fly ashes in the oxidation and retention of mercury

Abstract: During the combustion of coal in power plants Hg is released from the coal into the environment. Several technologies are under developed to reduce these emissions, but the need to implement new control systems will depend in part on the extent to which Hg can be

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 27 publications
(28 reference statements)
5
29
0
Order By: Relevance
“…The conclusion is consistent with the results of laboratory-scale experiments described above where interaction of Hg 0 with chlorine or HCl (creating HgCl 2 ) can enhance the Hg retention [247,264,273].…”
Section: Effect Of Operating Conditions In Power Stationssupporting
confidence: 92%
See 1 more Smart Citation
“…The conclusion is consistent with the results of laboratory-scale experiments described above where interaction of Hg 0 with chlorine or HCl (creating HgCl 2 ) can enhance the Hg retention [247,264,273].…”
Section: Effect Of Operating Conditions In Power Stationssupporting
confidence: 92%
“…FAs from hot-side ESP exhibited lower Hg content related to those collected under cold-side ESP. Fabric filter FAs contained generally higher Hg content than ESP ones (due to closer contact and intensive interaction between flue gas components and captured particles [273,282] in combination with lower retention temperature). When petroleum coke was co-combusted with coal, as a consequence of its low SSA, the Hg content was lower as well [181,275].…”
Section: Effect Of Uc Propertiesmentioning
confidence: 98%
“…Therefore this technique may help identify the product of mercury oxidation. Additionally, unburned carbon (UBC) and iron in fly ashes have been confirmed to be important for mercury oxidation and adsorption [19][20][21]. However, a systematical study on the roles of the fly ash compositions is still needed.…”
Section: Introductionmentioning
confidence: 97%
“…However, the high price that activated carbon can reach on the market, especially if it is impregnated with elements such as sulphur or choline, has encouraged efforts to find alternative adsorbents prepared from low-cost raw materials, such as agricultural residues, cheap biopolymers or waste tires, [4][5][6] and by-products from combustion plants, such as fly ashes. 7,8 In the present study mercury adsorption tests were performed using char samples obtained from the gasification of biomass (sunflower husks, poultry litter, wood and plastic-paper wastes). In previous studies, 9,10 some of these low-cost sorbents showed mercury retention capacities comparable to those of commercial activated carbons especially designed for the capture of Hg 0 in simulated coal combustion conditions.…”
Section: Introductionmentioning
confidence: 99%